2017
DOI: 10.1186/s12888-017-1407-y
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the short Arabic UPPS-P Impulsive Behavior Scale

Abstract: BackgroundImpulsivity is involved in numerous psychiatric and addictive disorders, as well as in risky behaviors. The UPPS-P scale highlights five complementary impulsivity constructs (i.e., positive urgency, negative urgency, lack of perseverance, lack of premeditation, and sensation seeking) that possibly work as different pathways linking impulsivity to other disorders. In this study, we aimed to evaluate the psychometric properties of the Arab language short 20-item UPPS-P scale and to eventually validate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 31 publications
(48 reference statements)
3
19
0
2
Order By: Relevance
“…We also explored the relationship between the five subscales and the variables for depression, anxiety, and demography. The results of our study and earlier studies suggest that the impulsivity trait can be influenced by depression and anxiety (9,14,28). In addition, some studies showed that impulsivity decreased as age increased, which was found here for lack of perseverance (8,31).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We also explored the relationship between the five subscales and the variables for depression, anxiety, and demography. The results of our study and earlier studies suggest that the impulsivity trait can be influenced by depression and anxiety (9,14,28). In addition, some studies showed that impulsivity decreased as age increased, which was found here for lack of perseverance (8,31).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, negative urgency was not notably correlated with a lack of premeditation; this has not been reported in previous studies. However, the low correlation between negative urgency and the lack of perseverance is common (27)(28)(29). The relationship between the various facets of impulsivity may vary in different countries because of cultural diversity.…”
Section: Discussionmentioning
confidence: 99%
“…The UPPS-P Impulsive Behavior Scale consists of 59 statements rated on a 1 to 4 Likert-type scale from “agree strongly” to “disagree strongly.” The UPPS-P questionnaire has been translated into more than 10 languages, including French [ 36 ], German [ 37 ], Italian [ 38 ], Spanish [ 39 ], Korean [ 40 ], Polish [ 41 ], Portuguese [ 42 ], and Dutch [ 43 ] and multiple short forms have been developed in Arabic [ 44 ], English [ 45 ], Farsi [ 46 ], French [ 47 ], German [ 48 ], Italian [ 49 ], and Spanish [ 50 ]. A child version also has been developed and validated [ 51 ].…”
Section: Development Of the Upps-p Model Of Impulsive Personalitymentioning
confidence: 99%
“…There is another short, 20-item version of the UPPS-P that was proposed by Billieux et al (2012) (translated into Spanish: Cándido et al, 2012 ; Italian: D’Orta et al, 2015 ; and Arabic: Bteich et al, 2017 ). To build this short scale the authors followed a different approach to that used by Cyders et al (2014) : they chose the four items with the highest factorial loads in their respective domains.…”
Section: Introductionmentioning
confidence: 99%